Regulation of FT splicing by an endogenous cue in temperate grasses - Zhengrui Qin (Nature Portfolio, 2017)
The correct timing of transition from the vegetative to reproductive stage is critical during the plant life cycle. Here the authors show that age dependent alternative splicing ofFLOWERING LOCUS T mRNA regulates phase transitions in Brachypodium distachyon.